Mental health in times of pandemic: A literature review (2021)
Society is going through a pandemic because of COVID-19 originating in Wuhan (China), which has triggered crises in all the nations of the world, which has transformed daily life, due to the measures taken by governments to stop the increase in infections. However, isolation, quarantine, concern, and fear of contagion and/or death have directly affected mental health. The research focused on identifying the main consequences of the pandemic and isolation on mental health, it was carried out from a qualitative methodology, under a bibliographic design, of a documentary type, the sample was of a theoretical type, made up of 58. Finally, it was found that there are population groups vulnerable to stress and various reactions of people to changes, however, mental health care has been underestimated and it is necessary to develop strategies to avoid generating an epidemic in the population about mental health.